HUBUNGAN LAMA PENGGUNAAN GADGET DENGAN PERILAKU SOSIAL ANAK PRASEKOLAH - Putri, Emri Oktaresa; Utami, Agnita; Lestari, Raja Fitrina (Universitas Ahmad Dahlan, 2020)
Gadgets are used by all people including preschool children. The use of gadgets in the pre-school increase every year and can make the child social behavior is impaired because addicted to gadget duration play with more than 1 hour. This study aims to see the long relationship between the use of gadgets and the social behavior of pre-school children. This type of research is quantitative using a description of correlation design with a cross-sectional approach. The sampling technique used was consecutive sampling with a sample of 76 respondents. The data collection tool used is a questionnaire. The results of this study indicate that as many as 46.1% of children use gadgets more than 1 hour every day and 27.6% of children have bad socialization behavior. Chi square correlation test results obtained Â = 0.003 (p <0.05), which means that there is a significant relationship between the duration of the use of gadgets and the social behavior of pre-school children in TK Negeri Pembina 3 Pekanbaru. The results of this study are expected to provide knowledge to parents who have pre-school children to limit children in using gadgets.